Disciplinary communities of practice for a greater gender equality in physics & life sciences - Reiland, S.; Palmén, R.; Kamlade, L. (My University, 2022)
This chapter reflects on how disciplinary specific Communities of Practice (CoPs) can be a useful vehicle to share knowledge, experience and practices to further gender equality in R&I organisations. This paper shares the experiences of two CoPs set up with specific disciplinary focuses, one on physics and the other on life sciences. There is a dearth of academic literature that looks at how disciplinary based CoPs can foster institutional change for gender equality in research and innovation institutions. This chapter is based on the observations of the two CoP facilitators (authors of this paper) as well as 10 semi-structured interviews carried out with CoP members. It reflects on some of the similarities and differences of the two disciplinary based CoPs – by charting their approaches to sharing knowledge, experience, and practices for gender equality and aims to strengthen the evidence-base on taking a disciplinary inter-organisational CoP approach to promoting institutional change for gender equality in R&I organisations.